PELATIHAN PENULISAN BUKU AJAR BAGI GURU PKn SMA SE KOTA SEMARANG - Titik Haryati; Rosalina Ginting; Suwarno Widodo; Kiki Aryaningrum; Bambang Kumoro (Universitas PGRI Semarang, 2011)
Abstract There are still a few handouts created by the teachers. In fact, teachers feel lazy to make a handout to succeed their teaching and learning process, especially civic teachers who are still low in understanding how to make and design their own handout. A handout is an instrument that teachers supposed to writing it. By writing a handout, teacher can explore his material based on the problems faced in the class. That is way; the Team thought that we need to give them something to train them in writing their own teaching handout. This community service was given to civic teachers of senior high school who has the important role in tranfering knowledge about civic subject. This activity had some sessions, there were; lecturing, discussion, questions answer and feedback. It hopes that by understanding the way in designing a teaching handout, they will be encouraged to make their own handout to support their teaching learning process in the classroom. ?é?á Key words : a teaching handout, a civic subject ?é?á